RELIABILITY OF A NEW METHOD TO ANALYSE (TACTO) TO QUANTIFY THE ATHLETES DISPLACEMENT - Serrano, João (2012)
This investigation was to assess the accuracy of the local position measurement (LPM) by a semi-auto tracking software (TACTO) using a single video camera. The TACTO software was used for digitalization and calibration. The reconstruction of virtual coordinates into real coordinates was made using DLT-2D (Planar direct linear transformation), with algorithms adapted from the ISB in ‚MATLAB’ software routines. Seventy-eight digitalization’s were made by six subjects during two weeks (thirteen digitalization’s carried out by each one). Correlation coefficient of Pearson (r) and the intra-class correlation coefficient (ICC) and the relative technical error of the measurement were use to analyze the relationship between the coordinates. The results, demonstrate the intra-operator and inter-operators reliability of the methodology used.